Técnicas de archivo y su incidencia en la gestión empresarial del Departamento de Nómina en la Hacienda San Luis del Cantón Baba - Valencia Jurado, Alinson Pamela (2020)
This case study deals with the problem generated within the Hcda payroll department. San Luis in relation to the organization of archives because they do not have appropriate techniques, thus generating organized spaces with relevant and coherent information on document management. For the preparation of this study, techniques such as observation and interviews were used to determine the causes that generate the problem itself, using instruments such as an observation sheet and a questionnaire that is easy for the interviewee to understand. Thanks to the results obtained, it was possible to verify that it is urgent that the department has tools that help to keep control of all the information that is manipulated, which must be relevant, discarding what has already completed its life cycle and the only thing that generates is the reduction of space. It was shown that by applying the document retention table, it helps to keep track and determine which documents should be removed. In addition to the use of applications such as Google Cloud for the storage of important files.